THE ROLE OF ENTREPRENEURIAL ATTITUDE AND OPPORTUNITY RECOGNITION ON ENTREPRENEURIAL INTENTION OF UNIVERSITY STUDENTS - Ledi, Klenam Korbla; Ameza-Xemalordzo, Enya; Owusu, Joseph (International Journal of Entrepreneurial Knowledge, 2022)
The study investigates the mediating role of entrepreneurial opportunity recognition on the relationship between entrepreneurial attitude and entrepreneurial intention among university students in Ghana. A structured questionnaire was administered to 500 university students in Ghana, and the data collected was analyzed using Amos. Structural equation modeling (SEM) was used to assess the hypothesized paths. The result indicated that entrepreneurial attitude had a substantial positive impact on both entrepreneurial intention and opportunity recognition among university students in Ghana. The result further indicated that entrepreneurial opportunity recognition positively affected university students’ entrepreneurial intention. The study further illuminated that entrepreneurial opportunity recognition mediated the relationship between entrepreneurial attitude and entrepreneurial intention. This implies that an entrepreneurial attitude increases the chances of opportunity recognition and self-employment propensity in Ghana. The study suggests that students should cultivate an entrepreneurial mindset and develop a healthy attitude toward entrepreneurship, enhancing the chances of identifying and pursuing business opportunities. The study contributes to the literature by focusing on and highlighting innate attributes that can possibly contribute to self-employment propensity.